2016
DOI: 10.1016/j.rmb.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Richness of insectivorous bats in a chaparral area in the municipality of Tecate, Baja California, Mexico

Abstract: EcologyRichness of insectivorous bats in a chaparral area in the municipality of Tecate, Baja California, MexicoRiqueza de murciélagos insectívoros en una zona de chaparral en el municipio de Tecate, Abstract Twenty species of bats have been reported in the state of Baja California, however, there is not much information available for this group due to the lack of local studies. Therefore, the objective of this study was to increase the knowledge about the actual existing chiropteran fauna in Tecate, Baja Cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Bats also differ in the height at which they fly above traps, which are typically set 1-4 m above ground level, and thus avoid them. Leon-Tapia and Hortelano-Moncada (2016) reported that in their study in Mexico, 12 species of bats were detected by using ultrasonic detectors, whereas only 5 species were trapped. Furthermore, trapping inevitably disturbs a bat's natural activity.…”
Section: Introductionmentioning
confidence: 99%
“…Bats also differ in the height at which they fly above traps, which are typically set 1-4 m above ground level, and thus avoid them. Leon-Tapia and Hortelano-Moncada (2016) reported that in their study in Mexico, 12 species of bats were detected by using ultrasonic detectors, whereas only 5 species were trapped. Furthermore, trapping inevitably disturbs a bat's natural activity.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, trapping of bats is not necessarily a good measure of the absolute numbers or number of species present (MacSwiney et al, 2008). For example, Leon‐Tapia and Hortelano‐Moncada (2016) reported that in their study in Mexico, 12 species of bats were detected by using ultrasonic detectors, whereas only five species were trapped.…”
Section: Introductionmentioning
confidence: 99%